495 Basal cell carcinoma demonstrates a T-cell exclusion immune phenotype in contrast to other anti-PD-1 therapy responsive cutaneous malignancies. (9th November 2020) - Gibney, Geoffrey; Xiu, Joanne; In, Gino; O'Day, Steven; Lutzky, Jose; Drabick, Joseph; VanderWalde, Ari; Poorman, Kelsey; Korn, W; Atkins, Michael
Abstract : Background: Basal cell carcinoma (BCC) is considered an immunogenic tumor based on the high tumor mutational burden (TMB), increased incidence in immunocompromised patients, and responsiveness to imiquimod, a toll-like receptor agonist therapy. However, anti-PD-1 immunotherapy response rates in patients with advanced BCC appear less than that seen with other advanced cutaneous malignancies. Molecular profiles of BCC tumors were analyzed to determine immune phenotypes and resistance mechanisms in comparison to other anti-PD-1 therapy responsive cutaneous malignancies. Methods: Next generation sequencing on DNA (NGS; NextSeq and Novaseq), PD-L1 immunohistochemistry (SP-142 and 28–8 antibody clones, cutoff >5% tumor staining) and mRNA gene expression level (Whole Transcriptome Sequencing, NovaSeq) data from BCC (N=69), melanoma (N=914), and cutaneous squamous cell carcinoma (SCC) tumors (N=165) at Caris Life Sciences (Phoenix, AZ) were analyzed. Tumor mutational burden (TMB) was calculated by counting all non-synonymous missense mutations that had not been previously described as germline alterations. Microenvironment cell population counter 1 was used to estimate cell population abundance in the TME. Gene set enrichment analysis (GSEA) was performed on transcriptomes. 2 Statistical significance was set at P value or false discovery rate (FDR) < 0.05. Results: Of the 69 BCC tumors with NGS data, the most frequent mutations were in PTCH1 (82%), P53 (73%) and ARID1A (42%); additional relevant mutations included SMO (18%), JAK1 (9%), PI3KCA (6%), APC (4%), and CTNNB1 (3%). TMB was significantly greater in BCC compared to melanoma (median 30.5 vs 12 mut/Mb, P<0.0001) and similar to SCC (median 29.5 mut/Mb, P=0.9389). PD-L1 positivity was 1/23 (4%) in BCC, 215/831 (26%) in melanoma, and 81/147 (56%) in SCC. Interferon gamma and T-effector immune gene analyses showed significantly lower expression in BCC compared to melanoma and SCC (e.g., IFNg TPM=0.26 (BCC) vs 0.65 and 0.58 (melanoma, SCC, both P<0.01). BCC demonstrated the lowest CD-8 T-cell fractions and the highest neutrophil and cancer associated fibroblast (CAF) fractions compared to melanoma and SCC. Angiogenesis and TGF-beta gene sets were enriched in BCC compared to melanoma (NES=1.5, FDR=0.046 and NES=1.35, FDR=0.055, respectively), but not compared to SCC (NES=0.90, FDR=0.57 and NES=0.94, FDR=0.60, respectively). Conclusions: While BCC tumors demonstrated a high TMB, a markedly lower level of adaptive anti-tumor immunity in comparison to other cutaneous malignancies was observed. T-cell exclusion mechanisms mediated through CAFs and desmoplasia, with upregulation of TGF-beta and angiogenic signaling, may play a role. Further investigation into abrogation of these mechanisms is warranted to develop improved anti-PD-1 based therapies for BCC. References: Becht E, Giraldo NA, Lacroix L, Buttard B, Elarouci N, Petitprez F, Selves J, Laurent-Puig P, Sautès-Fridman C, Fridman WH, de Reyniès A. Estimating the population abundance of tissue-infiltrating immune and stromal cell populations using gene expression. Genome Biol 2016; 17(1):218. Subramanian A, Tamayo P, Mootha VK, Mukherjee S, Ebert BL, Gillette MA, Paulovich A, Pomeroy SL, Golub TR, Lander ES, Mesirov JP. Gene set enrichment analysis: a knowledge-based approach for interpreting genome-wide expression profiles. Proc Natl Acad Sci U S A 2005;102(43):15545–50.